Importance of the Social Structures in Cowpea Varietal Demands for Women and Men Farmers in Segou Region, Mali - Sylla, Almamy; Yila, Jummai Othniel; Diallo, Sory; Traoré, Sékou (MDPI, 2023)
Cowpea is the second most consumed leguminous crop after groundnut in Mali. Its national production was 260,000 tons in 2018. It contributes to nitrogen fixation in the soil. The improved varieties of cowpea cultivars contain traits such as high grain yield, drought resistance, and early maturity. However, the adoption of improved cowpea varieties remains low. The non-participation and or non-consideration of the needs of men and women farmers in the varietal selection process contributed to the low adoption rate of improved cowpea varieties. This study aims to understand the gender dynamics and social structures within the communities. It examines its influence on the adoption of improved varieties of cowpea. Anchored on gender relations theories, gender and social structures are analyzed as the core frame for organizing social relations that guide and coordinate individuals’ actions in a given situation. Qualitative and quantitative approaches were applied to collect data from cowpea growers in 11 villages around the Cinzana Research Station. It emerged from the study that male farmers are quick adopters of newly released cowpea varieties because they are mainly more involved in trials, innovation platforms, field visits, demonstration plot activities, and FPVS than women. Women are less involved in these activities, except in sorting harvested cowpea grains and seeds in the Cinzana Research Station. Women’s participation in cowpea related-activities is determined by the rules and norms of physical mobility and the structures that control and guide social interactions and connections within and outside of households and communities. The study recommends efficient resource allocation within households and communities, and the set up of strong institutional frameworks (such as innovation platforms) to enable women in adopting new and improved cowpea varieties and to expand the available opportunities in the cowpea production system.